Knowledge and Completeness of Covid-19 Vaccination - Mamesah, Marline Merke; Saputera, Ariawan Wangsa; Wijaya, Hermanto; Kurniawan, afif (Journal of Health Management Research, 2022)
Background: Corona Virus Disease (Covid-19) is a new type of virus that attacks the body's immunity and can cause death. The death rate due to the virus varies, depending on the infected population, regulations applied by the government, and the availability of laboratory tests. Aims: This study aims to determine the relationship between knowledge of Covid-19 vaccination and the completeness of Covid-19 vaccination in the area of ​​Rt.06 Rw.03 Randu Barat, Sidotopo Wetan Village, Kenjeran District. Methods: This study uses a correlation study design with a Cross-Sectional approach. The research population was residents of RT.06 RW.03 Randu Barat, Sidotopo Wetan Village, Kenjeran District, with a sample of 47 respondents taken using a simple random sampling technique. The independent variable is knowledge of the covid-19 vaccination, the dependent variable is the completeness of the covid-19 vaccination. Data were collected using a questionnaire, with an ordinal data scale and analyzed using the Rank Spearman Correlation test (alpha 0.05). Results: The results showed that almost half of the respondents (47.7%) had good knowledge about Covid-19 vaccination, and most of the respondents (72.3%) had incomplete vaccinations. Based on the Spearman Rank test analysis showed that there was an opposite relationship between knowledge and completeness of vaccination (p 0.000 < 0.05), and the correlation coefficient was -0.453, meaning the strength of the correlation between the two variables was strong. Conclusion: There is a significant relationship between knowledge and completeness of vaccination. So, it is hoped that it can add insight into public knowledge and awareness regarding the willingness to vaccinate against Covid-19.